(untitled) (Scientific journal of the Fergana State University, 2026)
This study examines contemporary innovative approaches to teaching English as a Foreign Language. The article analyzes advanced pedagogical methodologies including Task-Based Language Teaching (TBLT), the Flipped Classroom model, gamification, and artificial intelligence tools. The research investigates the impact of various innovative methods on language learning outcomes, student motivation, and active engagement in the educational process.